Penerapan Agglomerative Hierarchical Clustering Untuk Pengelompokan Kabupaten/Kota di Provinsi Sumatera Barat Berdasarkan Potensi Sambaran Petir - Rahmadani, Rahmadani; Martha, Zamahsary (Universitas PGRI Semarang, 2026)
Lightning strike are an atmospheric phenomenon that pose significant risk to human safety and infrastucture, partuculary in topical regions sudh as Indonesia, inculding West Sumatra Province. Variations in geographical and environmental conditions contribute to differences in lightning strike potential across districts/municipalities. This study aims to classify districts/municipalities in West Sumatera Province based on their lightning strike potential in order to identify areas requiring higher mitigation priority. The classification was conducted using Agglomerative Hierarchical Clustering with Ward’s method based on three main variables including lightning density, rainfall, and population density. The result indicate that West Sumatera Province can be grouped into 4 cluster of lightning strike potential: low, moderate, high, and very high. The low-potential cluster consists of 6 districts/municipalities, the moderate-potential cluster consists 6 districts/municipalities, the gigh-potential cluster consisits 6 districts/municipalities, and the very high potential cluster contains only 1 municipality. These findings provide a systematic spatial overview of lightning strike potential levels and may serve as a basis for determining regional risk mitigation proirities and infrastructure protection strategies.